Grafting Ink for Direct Writing: Solvation Activated Covalent Functionalization of Graphene. Issue 19 (14th April 2022) - Xia, Yuanzhi; Sun, Li; Eyley, Samuel; Daelemans, Brent; Thielemans, Wim; Seibel, Johannes; De Feyter, Steven
Abstract: Covalent functionalization of graphene (CFG) has shown attractive advantages in tuning the electronic, mechanical, optical, and thermal properties of graphene. However, facile, large‐scale, controllable, and highly efficient CFG remains challenging and often involves highly reactive and volatile compounds, requiring complex control of the reaction conditions. Here, a diazonium‐based grafting ink consisting of only two components, i.e., an aryl diazonium salt and the solvent dimethyl sulfoxide (DMSO) is presented. The efficient functionalization is attributed to the combination of the solvation of the diazonium cations by DMSO and n ‐doping of graphene by DMSO, thereby promoting electron transfer (ET) from graphene to the diazonium cations, resulting in the generation of aryl radicals which subsequently react with the graphene. The grafting density of CFG is controlled by the reaction time and very high levels of functionalization, up to the failing of the Tuinstra–Koenig (T–K) relation, while the functionalization layer remains at monolayer height. The grafting ink, effective for days at room temperature, can be used at ambient conditions and renders the patterning CFG by direct writing as easy as writing on paper. In combination with thermal sample treatment, reversible functionalization is possible by subsequent writing/erasing cycles. Abstract : A grafting ink displays unprecedented capability for the covalent functionalization of graphene, achieving a functionalized monolayer with ultrahigh grafting density. The writing is simple, efficient, and reversible, making the patterned covalent functionalization of graphene straightforward.